Neurotransmitter transporters - Amara, Susan G. (Susan Gaye), 1954- (Methods in enzymology ;, 1998)
General Description of the Series: Neurotransmitter Transporters focuses on biochemical, electrophysiological, pharmacological, molecular, and cell biological approaches used to study neurotransmitter transport systems. The articles provide detailed descriptions of procedures that should enable the reader to understand how they are accomplished and to repeat or adapt them for their own experimental needs. This book is the first to focus on methods that have been the basis for the rapid development of this area. General Description of the Series: The critically acclaimed laboratory standard for more than forty years, Methods in Enzymology is one of the most highly respected publications in the field of biochemistry. Since 1955, each volume has been eagerly awaited, frequently consulted, and praised by researchers and reviewers alike. Now with more than 300 volumes (all of them still in print), the series contains much material still relevant today--truly an essential publication for researchers in all fields of life sciences. Key Features * The transport of CNS neurotransmitter transporters * Electrophysiological, biochemical, molecular, cellular biological, pharmacological, neurochemical, and structural approaches * Both plasma and vesicular carriers.